Computational Study of Hypersonic Flow Past Spiked Blunt Body Using RANS and DSMC Method. (2016) - Sebastian, Jiss J.; James, Sandeep Eldho; Suryan, Abhilash
Abstract: Hypersonic vehicles when moving at very high speeds experience the problem of drag and heating. One of the ways to reduce this drag and heating is by the use of an aerospike. In the present study, the flow around a blunted body fitted with an aerospike is analyzed using a commercial software ANSYS Fluent and an open source Direct Simulation Monte Carlo (DSMC) code, called as dsmcFoam in OpenFOAM, at a high Mach number (M=6) at different length to diameter ratios (L/D = 1.5, 2) at an angle of attack 0 o . The aerospike placed in front of the body replaces the strong detached shock wave ahead of the body with a system of weaker oblique shock waves. A recirculation region is developed between the shock and the blunt body, which acts like a streamlined profile, thus reducing the drag and wall heat flux.